Factores de riesgo y su relación con el desarrollo de bronquitis crónica en adultos mayores en la ciudadela la ventura cantón Babahoyo provincia Los Ríos durante el primer semestre 2017 - Tomala Salvatierra, Angelo Miguel (2017)
Worldwide, tobacco causes a mortality rate much higher which is attributed to the use of alcohol and illegal drugs altogether, having been reported for the year 2000 that tobacco killed nearly 5 million people in the world, close to 2 million and approximately 200 thousand illegal drugs alcohol, being considered as social drug that causes the largest number of deaths from diseases preventable in the world and being the gate of input which frequently introduces young people to other drugs. In the Ecuadoru, an estimated 9,000 deaths per year as a result of tobacco. The increase in mortality in smokers is directly proportional to the amount of cigarettes smoked, duration of the habit, depth of inhalation and nicotine content and consumed tobacco tar. It is estimated that every cigarette a person sucking takes seven minutes of life. In general, it is shown that smokers have a 70% higher mortality rate compared with non-smokers, as a result of different diseases. This relates mainly to cardiovascular diseases, cancer of lung, coronary heart disease, chronic bronchitis and pulmonary emphysema. Evidence shows that smoking is responsible for 90% of deaths from lung cancer, 75% of deaths from bronchitis and 25% of deaths from ischaemic heart disease.